What matters in stakeholderss' satisfaction the case of a nutrition improvement program in Laguna, the Philippines - Pinon, Caroline D.; Geges, Dhino B.; Visco, Emilia S.; Mendoza, Maria Emilinda T.; Amparo, Jennifer Marie S. (2024)
The prevalence of malnutrition has been a pressing social and health issue in the Philippines. The University of the Philippines Los Baños has been implementing the Barangay Integrated and Development Approach for Nutrition Improvement (BIDANI) program with local governments in mainstreaming nutrition improvement programs (NIP) as a critical component of rural development.
Keywords: Nutrition program